(untitled) (Revista Electrónica Calidad en la Educación Superior, 2022)
This paper present the partial results of an investigation carried out to design protocol for the implementation of a self-assessment model, taking as a case study the Business School careers at UNED. The results to be presented are aimed at justifying the need to have practical instruments, to implement a self-assessment model, during the period February 2020 to May, 2021. The main findings indicate that the people consulted know the terms of self-assessment process and self-assessment model, however, they lack practical tools to follow up on them.